The Influence Of Empowerment, Society Culture And Level Education Of Head Poor Household Towards Social Capital And Accessibility Of Information And The Impact For Welfare OF Poor Household in Batam City of Kepulauan Riau Province - Effendi, Syahril; ., Ujianto; Priyawan, Sunu (Archives of Business Research, 2018)
The Government's policy for tackling poverty both national and regional interests can be done start with the creation of new jobs, increased educational programs and skills, to the implementation of the programs like presidential instruction Village left behind, the establishment of family welfare Savings, cooperative efforts of family welfare, until Social Security Nets Project, Sub Development Program and others. Households living with many members with the head of household who can potentially lower degree kids will face a higher poverty risk than others. This research aims to demonstrate and analyze the influence of empowerment, society culture and level education of head poor household towards social capital and accessibility of information and the impact for welfare of poor household in Batam City of Kepulauan Riau Province. The population in the research this is 36.103 head poor household in Batam City of Kepulauan Riau Province and the sample numbered 244 people. This research uses of data analysis in SEM (Structure Equational Modeling) using the AMOS version 22. The results of the discussions can be concluded that community empowerment effect significantly to social capital, community empowerment effect significantly to accessibility of information, community empowerment not significant effect against The welfare of PH in Batam city, popular culture has no effect significantly to social capital, cultural Society has no effect significantly to information accessibility, society culture has no effect significantly to The welfare of the PH, PH Head influential Education Levels significantly to social capital in Batam city, education level of the head of the PH effect significantly to information accessibility PH, PH Head education level have no effect in significantly to the well-being of PH in Batam city, social capital has no effect against the welfare of the PH and the accessibility of information to the welfare of the PH. The Influence of Empowerment, Society Culture and Level Education of Head Poor Household Towards Social Capital and Accessibility of Information and The Impact For Welfare of Poor Household in Batam City of Kepulauan Riau Province.